Implementation of Named Entity Recognition with a Developing Question Answering System: A Case Study in the Merapi Volcano Museum - Khusna, Arfiani Nur; Putri, Okhy Kharisma; Saputra, Dimas Chaerul Ekty (Journal of Intelligent Computing & Health Informatics, 2022)
Merapi volcano museum is a place to get some information about active mountain activities, the general public can access the website page at mgm.slemankab.go.id. Indeed, visitors are given easy access, but the information provided by the website is not fully complete, causing visitors to feel dissatisfied. Based on the results of a questionnaire from 40 respondents, it was found that 50.55% of website visitors did not get the information they wanted. Therefore, in this research, we built a Question Answering System (QAS) using the Named Entity Recognition (NER) method that has been implemented into Telegram. To improve the performance of the QAS system, testing and analysis has been carried out with a "white box" approach. The results show that the QAS system has 3 regions and 3 independent paths, with path 1 being 1-2-3-4-11, path 2 being 1-2-3-4-5-6-7-8-11, and path 3 being 1-2-3-4-5-6-7-9-10-11. Based on the results of this study, all three paths can produce the correct answer.